Mapping Flood-Prone Zone Using CMA and NDWI in Muaradua District, South OKU - Rahmanita, Dwie; Idarwati, Idarwati (Universitas Negeri Gorontalo, 2025)
Flooding is a recurring disaster in Indonesia, especially in vulnerable areas such as Muaradua District, South Ogan Komering Ulu. This study aims to delineate flood-prone zones using an integrated approach that combines Composite Mapping Analysis (CMA) and the Normalized Difference Water Index (NDWI). Six environmental parameters river density, soil type, land cover, rainfall, elevation, and slope gradient were processed using Geographic Information Systems (GIS) to generate a vulnerability index. Sentinel-2 imagery was used to detect actual inundation through NDWI computation. The findings show that 43.08% of the study area is slightly vulnerable, 33.02% vulnerable, and 4.59% very vulnerable, while NDWI analysis revealed that 12.31% of the total area was inundated. High-risk villages such as Pasar Muaradua and Pancur Pungah exhibited flood exposure levels exceeding 29%. Spatial overlay analysis demonstrated strong concordance between model-based vulnerability and observed inundation, validating the robustness of the integrated method. These results provide critical input for spatial planning and targeted flood mitigation efforts in the region.